Construção moderna para uma congregação do século XX: o Mosteiro de Santa Maria do Mar das Beneditinas da Rainha dos Apóstolos - Casanova, Hugo (Lusitania sacra, 2023)
The project of the Monastery of Santa Maria do Mar (Sassoeiros) was carried out, from 1958, by the architects Nuno Teotónio Pereira (1922-2016), Nuno Portas (b.1934), Pedro Vieira de Almeida (1933-2011) with the collaboration of the landscape architect Júlio Moreira (b. 1930), for the religious congregation of the Benedictine Sisters of the Queen of Apostles. Nuno Teotónio Pereira's dialogue with the Benedictine sisters resulted in an exceptional functional architectural programme, which started with a preliminary study prepared as a "guide" (1958-1959) for the elaboration of the project, and developed into an architectural project carried out by six hands. Set in the context of the movement for the renewal of religious art - Movimento de Renovação da Arte Religiosa (1954-69) -, the Monastery of Santa Maria do Mar is a modern monastery to which we attribute heritage value, because it reflects the history of religious architecture and religious congregations in Portugal in the 20th century and attests to the spirit of dialogue between the Benedictine nuns and Nuno Teotónio Pereira's studio.